Analisis Beban Pencemar dan Kapasitas Asimilasi di Estuari Sungai Belau Teluk Lampung - Sembel, Luky (UNIVERSITAS SRIWIJAYA, 2012)
ABSTRACTUtilizationÃ‚Â aroundÃ‚Â ofÃ‚Â BelauÃ‚Â RiversÃ‚Â wasÃ‚Â diverse,Ã‚Â suchÃ‚Â asÃ‚Â agriculture,Ã‚Â industry,Ã‚Â households,Ã‚Â hotels,Ã‚Â markets,Ã‚Â residentialÃ‚Â populationÃ‚Â andÃ‚Â fishingÃ‚Â boats.Ã‚Â AccordingÃ‚Â toÃ‚Â theÃ‚Â explanation,Ã‚Â theÃ‚Â purposeÃ‚Â ofÃ‚Â thisÃ‚Â studyÃ‚Â wasÃ‚Â toÃ‚Â determineÃ‚Â distributionÃ‚Â andÃ‚Â concentrationÃ‚Â distributionÃ‚Â patternsÃ‚Â ofÃ‚Â Pb,Ã‚Â Cd,Ã‚Â andÃ‚Â CrÃ‚Â whichÃ‚Â evaluatedÃ‚Â fromÃ‚Â theÃ‚Â distributionÃ‚Â ofÃ‚Â salinity,Ã‚Â calculateÃ‚Â theÃ‚Â assimilationÃ‚Â capacityÃ‚Â inÃ‚Â marineÃ‚Â andÃ‚Â analyzingÃ‚Â theÃ‚Â directionÃ‚Â ofÃ‚Â environmentalÃ‚Â managementÃ‚Â EstuaryÃ‚Â BelauÃ‚Â atÃ‚Â LampungÃ‚Â Bay.Ã‚Â TheÃ‚Â dataÃ‚Â wasÃ‚Â analyzedÃ‚Â byÃ‚Â usingÃ‚Â theÃ‚Â viewÃ‚Â patternÃ‚Â ofÃ‚Â relationshipÃ‚Â betweenÃ‚Â dissolvedÃ‚Â heavyÃ‚Â metalsÃ‚Â andÃ‚Â salinityÃ‚Â throughÃ‚Â mixingÃ‚Â graphÃ‚Â approach.Ã‚Â Furthermore,Ã‚Â toÃ‚Â knowÃ‚Â theÃ‚Â pollutantÃ‚Â loadÃ‚Â andÃ‚Â capacityÃ‚Â ofÃ‚Â assimilationÃ‚Â wereÃ‚Â useÃ‚Â aÃ‚Â graphÃ‚Â ofÃ‚Â theÃ‚Â relationshipÃ‚Â betweenÃ‚Â theÃ‚Â concentrationÃ‚Â ofÃ‚Â eachÃ‚Â parameterÃ‚Â withÃ‚Â pollutantÃ‚Â loadÃ‚Â onÃ‚Â theseÃ‚Â parameters.Ã‚Â TheÃ‚Â resultsÃ‚Â analysisÃ‚Â ofÃ‚Â pollutantÃ‚Â loadsÃ‚Â andÃ‚Â assimilationÃ‚Â capacityÃ‚Â showedÃ‚Â thatÃ‚Â theÃ‚Â parametersÃ‚Â ofÃ‚Â TSS,Ã‚Â BODÃ‚Â andÃ‚Â CODÃ‚Â wereÃ‚Â stillÃ‚Â ableÃ‚Â toÃ‚Â performÃ‚Â selfÃ‚Â purification,Ã‚Â whereasÃ‚Â forÃ‚Â theÃ‚Â parametersÃ‚Â ofÃ‚Â nitrate,Ã‚Â phosphate,Ã‚Â Pb,Ã‚Â CdÃ‚Â andÃ‚Â CrÃ‚Â wereÃ‚Â unableÃ‚Â toÃ‚Â performÃ‚Â self-purification.Ã‚Â TheÃ‚Â managementÃ‚Â mustÃ‚Â beÃ‚Â builtÃ‚Â notÃ‚Â onlyÃ‚Â withinÃ‚Â theÃ‚Â autorityÃ‚Â ofÃ‚Â LampungÃ‚Â GovernmentÃ‚Â andÃ‚Â theÃ‚Â staffs,Ã‚Â butÃ‚Â alsoÃ‚Â mustÃ‚Â beÃ‚Â holisticÃ‚Â upstreamÃ‚Â toÃ‚Â downstreamÃ‚Â alongÃ‚Â theÃ‚Â riverÃ‚Â thatÃ‚Â involvesÃ‚Â severalÃ‚Â governmentÃ‚Â autority.Ã‚Â Keywords:Ã‚Â PollutionÃ‚Â LoadÃ‚Â ,Ã‚Â heavyÃ‚Â metals,Ã‚Â theÃ‚Â assimilationÃ‚Â capacity,Ã‚Â EstuaryÃ‚Â Belau